dada a função f(×)=2×+1.
f(0) f(7) f(-2) f(-5)
Soluções para a tarefa
Respondido por
1
f(x) = 2x + 1
f(0) = 2.0 + 1 = 0 + 1 = 1
f(7) = 2.7 + 1 = 14 + 1 = 15
f(-2) = 2.(-2) + 1 = - 4 + 1 = - 3
f(-5) = 2.(-5) + 1 = - 10 + 1 = - 9
f(0) = 2.0 + 1 = 0 + 1 = 1
f(7) = 2.7 + 1 = 14 + 1 = 15
f(-2) = 2.(-2) + 1 = - 4 + 1 = - 3
f(-5) = 2.(-5) + 1 = - 10 + 1 = - 9
iago146:
obg irmão
Respondido por
2
f(0)=2×0+1=1
f(7)=2×7+1=15
f(-2)=2×(-2)+1=-3
f(-5)=2×(-5)+1=-9
f(7)=2×7+1=15
f(-2)=2×(-2)+1=-3
f(-5)=2×(-5)+1=-9
Perguntas interessantes
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Ed. Física,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Ed. Física,
1 ano atrás